Transcriptome Analysis of Hypothalamic-Pituitary-Ovarian Axis Reveals circRNAs Related to Egg Production of Bian Chicken - Peifeng Li; Qi Zhang; Chengzhu Chu; Binlin Ren; Pengfei Wu; Genxi Zhang (Animals, 2024)
The hypothalamic–pituitary–ovarian (HPO) axis plays a pivotal role in the regulation of egg production in chickens. In addition to the traditional understanding of the HPO axis, emerging research highlights the significant role of circRNAs in modulating the functions of this axis. In the study, we collected hypothalamus, pituitary, and ovarian tissues from low-yielding and high-yielding Bian chickens for transcriptome sequencing. We identified 339, 339, and 287 differentially expressed (DE) circRNAs with p_value < 0.05 and |log2 (fold change)| ≥ 1 in hypothalamus, pituitary, and ovarian tissues. The Gene Ontology (GO) enrichment analysis for the source genes of DE circRNAs has yielded multiple biological process (BP) entries related to cell development, the nervous system, and proteins, including cellular component morphogenesis, cell morphogenesis, nervous system development, neurogenesis, protein modification process, and protein metabolic process. In the top 30 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, we observed the enrichment of the GnRH signaling pathway in both the hypothalamus and the pituitary, solely identified the GnRH secretion pathway in the pituitary, and discovered the pathway of oocyte meiosis in the ovary. Furthermore, given that circRNA primarily functions through the ceRNA mechanism, we constructed ceRNA regulatory networks with DE circRNAs originating from the GnRH signaling pathway, GnRH secretion, ovarian steroidogenesis, steroid hormone biosynthesis, and the estrogen signaling pathway. Finally, several important ceRNA regulatory networks related to reproduction were discovered, such as novel_circ_003662-gga-let-7b/miR-148a-3p/miR-146a-5p/miR-146b-5p and novel_circ_003538-gga-miR-7464-3p-SLC19A1. This study will contribute to advancements in understanding the involvement of circRNAs in the HPO axis, potentially leading to innovations in improving egg production and poultry health.